2017
DOI: 10.1007/s10877-017-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

The combination of indocyanine green clearance test and model for end-stage liver disease score predicts early graft outcome after liver transplantation

Abstract: Early allograft dysfunction (EAD) and early postoperative complications are two important clinical endpoints when evaluating clinical outcomes of liver transplantation (LT). We developed and validated two ICGR15-MELD models in 87 liver transplant recipients for predicting EAD and early postoperative complications after LT by incorporating the quantitative liver function tests (ICGR15) into the MELD score. Eighty seven consecutive patients who underwent LT were collected and divided into a training cohort (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Four of the six single-centre observational studies were prospective, and two were retrospective cohort studies. Only two studies tested the predictive ability of the prognostic factor in an internal validation cohort 29 , 30 . The recruitment method of participants was not always reported.…”
Section: Resultsmentioning
confidence: 99%
“…Four of the six single-centre observational studies were prospective, and two were retrospective cohort studies. Only two studies tested the predictive ability of the prognostic factor in an internal validation cohort 29 , 30 . The recruitment method of participants was not always reported.…”
Section: Resultsmentioning
confidence: 99%
“…In some previous studies, Olmedilla et al also found that a PCR level of <10–13%/min in the early post-transplant period was related to graft dysfunction [ 14 , 27 , 28 ]. In another study, conducted by Tian et al, 62 patients underwent PCR tests within 2 weeks following liver transplantation and the results showed a significant correlation among the levels of total bilirubin, pre-albumin, and albumin measured at different time points; therefore, the authors treated the declined value of PDR as an independent risk factor of graft dysfunction during the early post-transplant period [ 29 , 30 ]. It should be noted that PDR is affected by the volume of hepatic blood flow and the ability of the liver to eliminate ICG.…”
Section: Discussionmentioning
confidence: 99%
“…The ICG clearance test is a useful quantitative evaluation of liver function before transplantation. 97,98 Tang et al 98 found that the donor ICG retention rate at 15 m (ICGR15) before procurement was independently associated with survival at 3 months post-transplantation. That study also reported that the optimal donor ICGR15 cutoff was 11.0%/m and that it could be used as an early indicator of liver quality.…”
Section: Imagingmentioning
confidence: 99%